Challenges perceived by nursing professionals in physician‐centred organizations: An exploratory qualitative study. (27th January 2022) - Abbas, Sidra; Zakar, Rubeena; Fischer, Florian; Gilani, Amir
Abstract: Aim: To explore and analyse contextual challenges in nursing that have affected nurses' perceptions and role performance. Background: Health system hierarchy and patient/family‐centred care has led to a high demand for skilled nurses. However, patriarchal organizations create challenges for nursing clinicians in Pakistan and elsewhere. Methods: A qualitative exploratory research (phenomenology) design was used. Twenty‐five participants identified through purposive sampling contributed to the study. The data analysis was conducted using NVivo 12 Plus. We generated six major themes. Reporting was accomplished according to the consolidated criteria for reporting qualitative research checklist. Results: Gendered division of labour places nurses in a submissive position in clinical practice. Decreases in nurse‐to‐patient ratio and increase in patient‐focused care adversely affect evidence‐based practice. The gap between theory and practice in delivering quality care is increasing due to existing communication barriers among health‐related professionals and an inadequate work environment. Comparatively inactive nursing leadership and directorate roles are not improving the social image of nursing, and are promoting role conflict and poor nursing self‐concepts among nurses. In fact, cultural shock experienced by young nurses has produced inherent disorientation in their professionalism and fostered displays of horizontal violence towards them by senior nurses. Conclusion: These challenges are influencing nurses' decisions to remain in or to join nursing as a profession that is confronted by severe recruitment and retention shortages due to the social and cultural stigmatization of this female dominated profession. Implications for nursing, health and social policy: This study promotes the concept of evidence‐based practice to deliver quality health services in public hospitals and to improve the social status of nursing in Pakistan. It provides influential evidence to policymakers who should urgently address nurses' workplace health and safety issues as a global right.